Models of care for patients with knee osteoarthritis in primary healthcare: a scoping review protocol - Eduardo B Cruz; Helena Donato; Ana M Rodrigues; Daniela Costa; Daniela Gonçalves-Bradley; Luís A Gomes; Carla Nunes (BMJ Open)
Introduction Knee osteoarthritis (OA) is a prevalent condition with associated high disability and healthcare costs. Evidence of major gaps in the implementation of evidence-based interventions in people with knee OA led several healthcare systems to implement models of care (MoCs) in order to improve knowledge translation and guaranty their economic sustainability. Nevertheless, there are few studies that analyse the existing body of evidence of MoCs for patients with knee OA in primary healthcare settings. Therefore, we aim to identify MoCs developed for patients with knee OA implemented in primary healthcare and, analyse their core components and outcomes. This scoping review will create knowledge about the components and outcomes of these MoCs which, in the future, will facilitate their transferability to practice.Methods and analysis We will include studies that developed and implemented an MoC for people with knee OA in primary healthcare. We will use the PCC mnemonic, being ‘Population’—people with Knee OA, ‘Concept’—the MoCs and ‘Context’—the primary healthcare setting. We will conduct the search on PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Scopus, Web of Science Core Collection, as well as grey literature databases and relevant institutions and organisations websites, for articles published after 2000. Two independent reviewers will screen titles and abstracts followed by a full-text review to assess papers regarding their eligibility. We will evaluate the methodological quality of the included studies with the Mixed Methods Appraisal tool and apply a data abstraction form to describe and interpret the evidence.Ethics and dissemination As a secondary analysis, this scoping review does not require ethical approval. Findings will be published in peer-review journal, presented in scientific conferences and as a summary through primary healthcare units.